Northeast Indian Enigmas. (August 2017) - Kolås, Åshild
The standard frame of security studies is to view Northeast India as a site of multiple "ethnic conflicts." In trying to unravel these conflicts, the focus has remained on the fault lines between the state and its alleged contenders, the region's multiple nonstate actors. This special issue tries to look at the conflict scenario of Northeast India through a different set of lenses, in an effort to draw the focus away from the usual conflict histories, to direct attention toward the ideas that underpin the construction of Northeast India as a frontier zone and its people as "others, " both internally divided and divided from the Indian mainstream. The "tribal" movements of Northeast India, and the patterns of conflict associated with them, are well researched. What this issue explores is how and why tribal political projects are created and pursued, and how to understand these projects, whether as strategies of resistance and survival, identity politics, or rival projects of extraction and exploitation. What do we find when we look into the enigmatic frontier as a "zone of anomie, " a "sensitive space, " or a parapolitical scene that defies the taken-for-granted dichotomies between the state and nonstate?